Pengaruh Karakteristik Chief Executive Officer Terhadap Nilai Perusahaan di Indonesia - Hidayat, Muhammad; Siregar, Muhammad Ichsan; Aspahani; Erman, Ery (Politeknik Ganesha Medan, 2024)
The aim of this research is to see the influence of CEO characteristics on company value. The population of this study is 825 companies listed on the Indonesian Stock Exchange in 2022. The sampling technique used was purposive sampling. 578 companies were sampled in this study. Documentation techniques are used in data collection, the data is obtained via the www.idx.co.id page. The data analysis technique used is multiple linear regression. The research results show that gender, age and tenure have a significant effect on company value, while education and nationality do not have a significant effect. These results indicate that the role of female CEOs has a more positive influence in generating positive value for the company. Where investors feel confident that female CEOs will pay more attention to the results they achieve. These results also indicate that CEOs who have been in a leadership position in a company for a long time will be more careful in making decisions, where the longer a CEO has been in a company, the more the decisions taken will increase the value of the company in the eyes of investors and stakeholders. These result indicate that the age of a CEO has a significant negative effect on company value, where the older a CEO is, the more the company value decreases